A Development Approach to Conflict-Induced Internal Displacement - World Bank (World Bank, Washington, DC, 2021)
The approach paper provides the rationale for further integration of conflict-induced internally displaced persons (IDPs) into World Bank Group (WBG) programming based on its commitment to vulnerable and marginalized populations. It highlights the conflict sensitive engagement required to address the needs of these populations. The purpose of this approach paper is to highlight the key principles for World Bank Group (WBG) engagement to address conflict-induced internal displacement. It provides the rationale for inclusion of IDPs in WBG programming based on its commitment to vulnerable and marginalized populations, while highlighting the conflict-sensitive engagement required to address the needs of these populations. The new World Bank Group Strategy for Fragility, Conflict and Violence (FCV), endorsed in February 2020, identifies support to situations of internal displacement as a priority area. This approach paper is also situated in the broader context of the WBG agenda to support people on the move due to urbanization and economic migration, as well as those displaced due to natural disasters and the effects of climate change.